Investigation on Nucleation Kinetics of Bimetallic Non-linear Optical CdHg(SCN)4 Single Crystals - Rajesh Kumar, T.; Sagayaraj*, P. (Asian Journal of Chemistry, 2011)
The metastable zone width and the nucleation parameters such as interfacial energy, radius of the critical nucleus and volume of free energy have been carried out for an efficient thiocyanate ligand based bimetallic non linear optical cadmium mercury thiocyanate single crystal. Cadmium mercury thiocyanate was synthesized and the solubility of the synthesized salt was determined in two different solvents at varying temperatures. The metastable zone width study was carried out for different supersaturation levels. The induction period measurements have been carried out and the critical nucleation parameters are evaluated based on the classical theory of homogeneous nucleation. Using the experimentally determined induction period values, the interfacial energy was estimated. Bulk single crystals of cadmium mercury thiocyanate have been grown in ethanol: water mixed solvent by employing slow cooling method. The grown crystals were characterized by single crystal XRD and UV-Vis spectroscopic techniques.